Hubungan Konsep Diri dengan Prestasi Akademik pada Mahasiswa Keperawatan - Prabawati Setyo Pambudi; Diyan Yuli Wijayanti (Jurnal Keperawatan Diponegoro, 2012)
The self-concept is all forms of belief, feeling, and judgment of individuals believed about him and influence the process of social interaction with their surroundings. The self-concept also influences academic achievement. The self-concept has correlation with motivation. Students with high self-concept will tend to motivation to achieve goals. Students with less self-concept will tend to lose motivation and interest, which in turn impact the academic achievement. Previous studies by Jamaludin, Mazila, and Aminuddin (2011) obtained results from 106 students as much as 84.9% (90 students) have a negative self-concept. This research aimed to determine the characteristic and the relationship between self-concept with academic achievement among students who achieved School of Nursing Faculty of Medicine Diponegoro University VI semesters. This study used a non-experimental quantitative research design with descriptive-correlation type. The research used total sampling with 65 respondents. The data was collected by questioners. The results of the chi square test was χ2 = 14.814 and p-value = 0.001 (p< 0,05) so there was a correlation between self-concept and academic achievement. It means that if the self-concept is good, the academic achievement is also good. Otherwise, if the self-concept is less, so the academic achievement is also bad. Educational institutions should consider the self-concept of students in the learning process